Science, innovation and business - Carnaby, Garth (New Zealand Science Review, 2011)
​I would like to talk to you about two cultures within the field of R&D – on the one hand, the culture of scientific research, and on the other, the culture of technological development for industry. These two activities and their associated cultures are not the same, nor indeed are their underlying purposes. This disparity of purpose flows through into the motivations which drive those who engage in each activity, and should be reflected in the excellence criteria used to assess performance. In New Zealand we have for many years confused these two activities, their purposes, their cultures, and indeed our systems of recognition for achievement in them. Much of this confusion has come from within the research community itself, stemming in some cases from unfamiliarity with the other field, in others from self interested promotion of one activity at the expense of the other, and in the worst cases intellectual snobbery and condescension reinforced by the review of peers unevenly selected from one culture or the other. Unless we are able to address this confusion here in New Zealand we will continue to have an innovation system which under-performs and an economy which does not meet our expectations.